Analisis Kemampuan Berpikir Komputasi Mahasiswa melalui Penggunaan Aplikasi Math Master - Qori Aulia Hafni Nasution; Yahfizham Yahfizham (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aims to analyze the impact of using the Math Master application on students' computational thinking skills. Computational thinking includes algorithmic thinking, logic, and problem-solving—essential abilities in learning mathematics. This research employed a descriptive quantitative approach with a questionnaire consisting of 10 statements, involving 30 student respondents. The results indicate a strong and significant relationship between the use of Math Master and students' computational thinking abilities. With a coefficient of determination of 56%, the application contributes positively to enhancing students' problem-solving and logical thinking skills. Therefore, Math Master is considered an effective alternative learning medium to support mathematics instruction in higher education.